Individual and group parameters of Rumex alpinus L. (Polygonaceae) as an indicator of the degree of disturbance to the Carpathian high-mountain meadow ecosystems (CHORNOMORSKI BOTANICAL JOURNAL, 2021)
Individual (height of flowering shoot, length of rhizome segments and their number on a growth axis) and group parameters (cover, density of immature individuals, flowering and vegetative shoots) of a clonal tall-herb species Rumex alpinus were studied in the populations undergoing different stages of anthropogenic succession in the Carpathians. The species can form dense Rumiceta alpini ruderal communities on the manured soil near the livestock camps. Rumex alpinus has a long life span and thick long-living rhizomes in which the segments’ size reflects the viability of the individual in previous years. The studied parameters characterize the extent of disturbance in grassland ecosystems on different stages of their anthropogenic or restoration succession. A significant number of immature individuals of seed origin proves the young age of a population and indicates the degrading vector of changes in ecosystems. However, the individuals of seed origin (particularly, immature) are almost or completely missing in the established dense Rumiceta alpini because clonal reproduction prevails there. The highest individual and group parameters of R. alpinus have been registered in the sites that are manured. Cessation of anthropogenic impact results in thinning out of populations and their gradual decline. Annual increments of rhizomes demonstrate a successive increase in the invasive populations and decrease in the regressive ones. R. alpinus is also a component of some native undisturbed communities where it shows moderate viability of individuals and low population density. Thus, high values of individual and group parameters of this species indicate significant disturbance of the area and its low conservation value, while its infrequent occurrence only in some solitary small sites can reflect an absence or low level of devastation of a mountain grassland ecosystem.
Keywords: anthropogenic impact, succession, rhizome segments, mountain meadows, Rumicetum alpini.